Factors That Influence Msme Decisions In Medan In Choosing Financing Sources For Business Capital - Rohima, Rohima; Bi Rahmani, Nur Ahmadi; Syahbudi, Muhammad (Universitas Ibn Khladun Bogor, 2025)
The objective of this research is to examine the determinants that affect decision-making processes among MSMEs in choosing a source of financing, both from formal institutions such as banks and non-formal institutions such as cooperatives and individual loans. The result is based on the research conducted, MSMEs’ decisions in selecting sources of business capital financing are more influenced by factors such as ease of access, speed of disbursement, and low administrative requirements than by rational considerations regarding profit margins. Although non-bank financial institutions such as cooperatives, fintech lending, and community loans offer higher profit margins, MSMEs still tend to choose them due to the simpler and less bureaucratic application process. This indicates that MSMEs’ decisions are pragmatic, prioritizing immediate benefits in business operations over long-term cost efficiency. This finding aligns with decision theory and pecking order theory, where business actors choose the most accessible financing option first, even though it carries greater risk.